Cellulase, mannanase and xylanase as novelty mixed enzyme RT-P3 powder through solid-state fermentation from copra meal residue for fed-batch ethanol fermentation - Siwarasak, Pongsri; Pajankate, Pradabrat; Pleanjai, Somporn (Journal of Applied Research on Science and Technology (JARST), 2016)
The objective of this study is to investigation of mixed enzyme RT-P3 such as mannanase, xylanase and cellulase from solid-state fermentation from copra meal residue using co-culture of Trichoderma reesei and Saccharomyces cerevisiae and the application of mixed enzyme RT-P3 powder in batch and fed-batch ethanol fermentation. The suitable condition of fresh mixed enzyme RT-P3 was 100 g copra meal residue and adjusted to 78 %w/w initial moisture content by 300 mL of 3% sugar in liquid medium pH 5 with included initial co-culture microorganism of 7.07×105 cell/mL and incubated at 24±2oC for 6 days. After that this mixed enzyme was dried at 65oC in a dryer to obtain powder at 7% w/w moisture content before used for ethanol fermentation through consolidate bioprocessing. It was found that the maximum ethanol was 33.0 and 47.7 g/L of batch and fed-batch fermentation respectively at 4 days incubation and room temperature (30oC).